Nursing education on collaborative discharge planning and motivating patients to control for further care and management - Dewi Kusumaningsih; Muhammad Agustianda (Malahayati International Journal of Nursing and Health Science, 2019)
Background: Nurse as a health worker had a role as educators. The role of nurse educators could be seen from 10 inpatients resulted there were 4 inpatients (40%) stated that nurses did their roles accurately and 6 patients (60%) stated that there were nurses didn’t their roles properly. This condition could cause an increasing amount of patients who uncontrolled  at Dr. A. Dadi Tjokrodipo Hospital  Bandar Lampung.Purpose: To know there was a correlation of nursing education on collaborative discharge planning and motivating patients to control for further care and managementMethods: This research was quantitative method. The design of this study was an analytical survey with a cross-sectional. The samples used in this study were 136 people. Collecting data sampling used a consecutive sampling. The statistical test used a chi-square test.Results: The roles of nurse educator which had not good categories were 73 respondents (53.7%) and the roles of nurse educator which had good category were 63 respondents (46.3%). Low control motivations were 69 respondents (50.7%) and high control motivations were 67 respondents (49.3%). The results of data analysis using the chi-square test showed p-value = 0.001.Conclusion: There was a correlation of the roles of the nurse educator in discharge planning with motivation of inpatients for control. It was expected that the results of this study could be used as material for consideration and input for the hospital to be able to know the importance of the role of nurse educators in discharge planning.